2017
DOI: 10.1111/aji.12661
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and fetal programming: A review of recent scientific advances

Abstract: We sought to synthesize a comprehensive literature review comprising recent research linking fetal programming to fetal telomere length. We also explored the potential effects fetal telomere length shortening has on fetal phenotypes. Utilizing the PubMed database as our primary search engine, we retrieved and reviewed 165 articles of published research. The inclusion criteria limited the articles to those that appeared within the last ten years, were pertinent to humans, and without restriction to language of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 32 publications
(41 reference statements)
0
27
0
Order By: Relevance
“…None of the nutritional factors showed a direct association with cord blood rTL, but in an additional model we further adjusted model 2 for placental rTL. Because previous studies have indicated sex-specific interactions with newborn rTL ( 14 ), we tested for a multiplicative interaction between fetal sex and the different nutrition markers in the adjusted models and performed stratified analyses. We carried out sensitivity analysis (model 4) adjusting for paternal age instead of maternal age in the adjusted models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the nutritional factors showed a direct association with cord blood rTL, but in an additional model we further adjusted model 2 for placental rTL. Because previous studies have indicated sex-specific interactions with newborn rTL ( 14 ), we tested for a multiplicative interaction between fetal sex and the different nutrition markers in the adjusted models and performed stratified analyses. We carried out sensitivity analysis (model 4) adjusting for paternal age instead of maternal age in the adjusted models.…”
Section: Methodsmentioning
confidence: 99%
“…This is important to study, since TL at birth is a main predictor for TL throughout life ( 6 , 9 , 10 ), and TL later in life is associated with the risk of several outcomes, such as cancer and cardiovascular diseases ( 11 , 12 ). There is emerging evidence that factors such as maternal stress ( 13 , 14 ), inflammation ( 15 ), gestational diabetes ( 16 ), exposure to air pollution ( 17 , 18 ), tobacco smoke ( 19 ), and toxic metals ( 20 ) may influence offspring TL.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, fetal or developmental programming may influence an individual’s susceptibility or propensity for disease in later life ( Entringer et al, 2018 ). A recent systematic review demonstrated that maternal factors such as age, exposure to chemicals (e.g., smoking), and maternal stress during pregnancy and nutritional and sleep disorders are related to the stimulation of telomeres in fetal cells ( Whiteman et al, 2017 ). Also, it has been documented that if TL is reduced in the newborn, the susceptibility to the development of chronic diseases in adulthood is increased ( Entringer et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the main characteristics of senescent cells is the production of inflammatory cytokines, which indicates a possible role of cellular senescence as an effector pathway that converges to trigger parturition. Intrinsic and extrinsic stressors that induce variation in prenatal exposures and maternal states and conditions, such as cigarette smoking, air pollution, diabetes, obesity, oxidative stress, and inflammation are associated with cellular aging, evidenced by the shortening of telomeres in fetal cells ( Whiteman et al, 2017 ). Thus, characteristics of maternal health status and behaviors during pregnancy may influence the individual’s susceptibility or propensity to disease in later life.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, as shown in Figure 2, there are different mechanisms through which TL is determined at different developmental stages. During pregnancy, TL is determined by genetics, by direct epigenetic-like transmission from the germ line, and by the prenatal sociodemographic factors of environment and nutrition (Whiteman et al 2017), as well as by stress exposures. Hematopoietic stem cells are determined during the first few months of development (Entringer et al 2012).…”
Section: Intergenerational Transmission Of Telomere Lengthmentioning
confidence: 99%